2007
DOI: 10.1016/j.arth.2006.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Tight Fit Technique in Primary Hybrid Total Hip Arthroplasty for Patients with Hip Dysplasia

Abstract: This paper presents the mid-term results of hybrid total hip arthroplasty for patients with hip dysplasia using a tight fit technique for the femoral component. We followed 113 hips in 99 patients for a mean of 11 years. All final femoral rasps used in this study over-rasped by 0.5 -1.0 mm for stem insertion, resulting in relatively thin cement mantles. Both components of one hip were removed due to infection. The other 5 acetabular components were revised for osteolysis, recurrent dislocation, or dislodgement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
(27 reference statements)
1
4
1
Order By: Relevance
“…The complication rate in our series is comparable with that reported in other studies of THA for dysplastic hips [17][18][19][20][21][22][23]. Limb length discrepancy is one of the main problems in severely dysplastic hip replacement, since functional lengthening is limited by tight soft tissues, especially by the sciatic nerve.…”
Section: Discussionsupporting
confidence: 90%
“…The complication rate in our series is comparable with that reported in other studies of THA for dysplastic hips [17][18][19][20][21][22][23]. Limb length discrepancy is one of the main problems in severely dysplastic hip replacement, since functional lengthening is limited by tight soft tissues, especially by the sciatic nerve.…”
Section: Discussionsupporting
confidence: 90%
“…We previously reported good intermediate-term results of the primary hybrid THA for patients with osteoarthritis secondary to developmental dysplasia [18,19]. Other authors also reported similar good results of hybrid THAs for patients with developmental dysplasia [20,21].…”
Section: Discussionmentioning
confidence: 54%
“…There was no aseptic loosening of the cemented stems in our study. Our consistent surgical techniques including "tight-fit technique", in which all final femoral rasps used for canal preparation over-rasped only by 0.5 mm, seem to have contributed to the good clinical results [18,19]. Several studies have reported increased rates of dislocations in patients with RA.…”
Section: Discussionmentioning
confidence: 80%
“…Orthopedic residents performed all surgery supervised by the senior author, a hip specialist. After rasping the canal, the stem was inserted with canal-filling (tight-fit) implantation [14][15][16]. The thirdgeneration cementing technique was applied, using 80 g of Surgical Simplex P bone cement (Stryker Howmedica Osteonics, Mahwah, New Jersey) mixed with 2 g of cephazolin immediately before cementing.…”
Section: Methodsmentioning
confidence: 99%